Chinese Expert Consensus on the Diagnosis and Treatment of Inflammatory Myofibroblastic Tumor - Xiaoyan Si; Shafei Wu; Rui'e Feng; Xuan Wang; Hui Guan; Jia He; Xuan Zeng; Wei Song; Shanqing Li; Ke Hu; Zhiyong Liang; Fuquan Zhang; et al. (Thoracic Cancer)
ABSTRACT Inflammatory myofibroblastic tumor (IMT) is a rare spindle‐cell neoplasm. IMT currently suffers from a paucity of standardized diagnostic and therapeutic guidelines. The Chinese expert consensus committee on the diagnosis and treatment of IMT formed an “Expert consensus on the diagnosis and treatment of inflammatory myofibroblastic tumor”. This consensus was developed through a comprehensive synthesis of expert opinions, an extensive review of the literature, and a series of offline and online deliberations. The committee aspires that this consensus will enhance the therapeutic outcomes and prognosis for patients with IMT in the future.